2021
DOI: 10.1002/er.6537
|View full text |Cite
|
Sign up to set email alerts
|

Isopropyl palmitate integrated with plasterboard for low temperature latent heat thermal energy storage

Abstract: Summary In recent years, the latent heat thermal energy storage using phase change materials (PCMs) has become a hot topic; it has attracted much attention in the utilization of renewable energy sources to improve the energy efficiency of buildings. Isopropyl palmitate (ISOP) with phase transition temperature of 10°C to 13°C and heat of fusion of ~113 J/g was selected to be used as a PCM in building applications. ISOP, 15%, was mixed with plasterboard (PB) as a building material in two techniques, immersion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Isopropyl palmitate, an ester of isopropyl alcohol and palmitic acid, is an interesting proposal among the PCMs and is considered an eco-friendly material. Its phase transition temperature lies between 283 K and 286 K and the heat of fusion is ~113 J/g [5], so it is adequate to be used as a PCM in thermal energy storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…Isopropyl palmitate, an ester of isopropyl alcohol and palmitic acid, is an interesting proposal among the PCMs and is considered an eco-friendly material. Its phase transition temperature lies between 283 K and 286 K and the heat of fusion is ~113 J/g [5], so it is adequate to be used as a PCM in thermal energy storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…The burning of PCMs can produce enormous amounts of smoke, flame, and hazardous fumes, which can be easily transmitted through the building, resulting in deaths, injuries, and property losses as Alkhazaleh et al reported in literature [12,13]. The flammability of organic PCM is regarded as the most serious hazard to its application in structures [14,15]. Previous research has shown that physically combining PCMs with flame retardants, such as intumescent flame retardants [16], magnesium hydroxide [17], and montmorillonite [18], can greatly improve their fire-retardant capabilities.…”
Section: Introductionmentioning
confidence: 99%